Daya Awet Wadi Ikan Toman (Channa micropeltes) Setelah Proses Fermentasi - Restu Restu (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2013)
Fish processing generally aims to maintain freshness, preserve, create products that have physical and chemical properties different from the original, but still liked by the community, enriching processed fishery products by utilizing materials that can not be marketed in the fresh form. This study aims to determine the durable of products wadi from toman fish meat after washing effect on the taste of salted wadi, in order to obtain the ideal preservation, therefore, the community can adopt it. Research results showed that treatment B give best result of durable of wadi from toman (Channa micropeltes) with nutritional value as follows: protein = 18.21%, Fat = 1.82%; organoleptic value is 7.02.